Time management - Williams, Kate; Reid, Michelle , 1979- (Pocket study skills, 2011)
"This easy-to-use guide helps students to improve their time management skills. Focusing specifically on challenges posed within a higher education context, it provides practical advice for students at all levels. Concise yet effective, the book?s informal style is supplemented by engaging illustrations"-- Provided by publisher.